Sobre o estilo de kung-fu garra de águia - Rafael Carvalho da Silva Mocarzel (Universidade Estadual do Oeste do Paraná, 2018)
As a millenarian practice, Kung-Fu is an object of difficult study when one observes the great historical-sociocultural transformations that took place in China. This fact is further aggravated when one searches for academic sources of origin or even for trust outside the Chinese language. The objective of this work was to present a historical review of a popular Kung-Fu style with almost a thousand years of existence - the Eagle Claw. Methodologically, this study is of a qualitative nature and has made use of the revision of literature and oral narratives with the Master of the style today in the world. It was possible to observe several direct and indirect influences of political, social and cultural order in the history of the style and its practitioners until the present day.